Pablo E. Saracino. Lorenzo de Padilla: un cronista anónimo del siglo XVI - Francisco Bautista (Universitat de Girona; Universitat Autònoma de Barcelona, 2016)
Pablo E. Saracino Lorenzo de Padilla: un cronista anónimo del siglo XVI Buenos Aires, Miño y Dávila, 2016. 127 p. ISBN 978-84-16467-24-2